2015
DOI: 10.1007/s11248-015-9882-8
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic mouse model for the in vivo bioluminescence imaging of the expression of the lysophosphatidic acid receptor 3: relevance for inflammation and uterine physiology research

Abstract: Lysophosphatidic acid (LPA) is a lipid-derived signaling molecule that plays key roles in diverse biological processes including inflammation and uterine remodeling. Although the function of LPA and its receptors has been extensively studied using knock-out mice, the temporal-spatial expression of LPA receptors is less well-characterized. To gain further insight into the dynamic regulation of LPA receptor 3 (Lpar3) expression in vivo by bioluminescence imaging, we generated and characterized mice transgenic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…12 LPA also played a crucial role in various biological processes such as inflammation and uterine remodeling. 30 A previous study showed that exogenous LPA contributed to inflammatory responses by modulating the expression of cytokine and its receptors of lung epithelial cells, which was in consistency with ours. 31 LPA4 can couple to Gα12/13, which activates Rho/ROCK, inducing neurite retraction and stress fiber formation with activation of other LPARs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…12 LPA also played a crucial role in various biological processes such as inflammation and uterine remodeling. 30 A previous study showed that exogenous LPA contributed to inflammatory responses by modulating the expression of cytokine and its receptors of lung epithelial cells, which was in consistency with ours. 31 LPA4 can couple to Gα12/13, which activates Rho/ROCK, inducing neurite retraction and stress fiber formation with activation of other LPARs.…”
Section: Discussionsupporting
confidence: 91%
“…For example, LPAR4 was a potential regulator of malignant behavior in head and neck squamous cell carcinoma cells and a potential therapeutic target . LPA also played a crucial role in various biological processes such as inflammation and uterine remodeling . A previous study showed that exogenous LPA contributed to inflammatory responses by modulating the expression of cytokine and its receptors of lung epithelial cells, which was in consistency with ours .…”
Section: Discussionsupporting
confidence: 89%
“…LPA 3 prefers 2-acyl-LPAs containing unsaturated fatty acids[ 83 ]. It mediates the activation of a series of physiological processes such as male and female reproductive physiology, inflammation, cell Ca 2+ homeostasis and cAMP regulation[ 107 , 117 - 119 ]. LPA 3 appears to determine vertebrate left-right patterning during embryogenesis as downregulation of Lpar3 or inhibition of LPA 3 activity disrupted patterning process in zebrafish[ 120 ].…”
Section: Lpa Receptors-mediated Lpa Signalingmentioning
confidence: 99%
“…Lpar3 -/- mice are viable with no reported neural deficits, even though LPA 3 is found in the frontal cortex, hippocampus, and amygdala[ 83 , 116 ]. On the other hand, female Lpar3 -/- mice have a delayed embryo implantation, and reduced litter size[ 117 ].…”
Section: Lpa Receptors-mediated Lpa Signalingmentioning
confidence: 99%